Strategi Pengembangan Ekowisata dalam Mendukung Konservasi Lingkungan - Nabila Zahra Hanum (Tourism and Hospitality Research, 2025)
Ecotourism has emerged as a sustainable alternative to mass tourism, offering a way to balance economic development and environmental conservation. This study explores strategic approaches to ecotourism development that actively support environmental conservation efforts. Employing a qualitative descriptive method, data were collected through field observations, interviews with stakeholders, and a review of relevant literature. The research was conducted in a protected natural area in Indonesia that has recently promoted ecotourism initiatives. Findings suggest that community involvement, environmental education, regulation enforcement, and infrastructure development are crucial components of successful ecotourism strategies. The study highlights how properly implemented ecotourism can increase conservation awareness, reduce environmental degradation, and provide sustainable livelihoods for local communities. These findings can inform policymakers and stakeholders in designing ecotourism policies that are both ecologically and economically beneficial.